ЗАҢНАМАЛЫҚ АКТІЛЕРДІҢ МӘТІНІН МЕМЛЕКЕТТІК ТІЛГЕ АУДАРУҒА БАЙЛАНЫСТЫ ӨЗЕКТІ МӘСЕЛЕЛЕР - Ilyassova , Гульжазира Актуреевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2017)
Relevance of the subject consists of the problems' researches connected with the legal equipment in the relations to quality of the acts' translations on a state language. Nowadays in the modern Kazakhstan legislation, as specified in article, problems connected with the low-quality text translation of the statutory legal acts exist still. At implementation of professional activity lawyers always make mistakes connected with the wrong text translation of the legal rules and legal terminology into Kazakh, for example, a direct transfer of the text is made and the meaning of legal terms is lost, the conventional legal terms are translated in several options. These problems result in the wrong understanding and interpretation of the legal rules. According to the theory of the law, necessary conditions of the legal equipment are respect for unity of terminology, inadmissibility of use in different terms for designation of the same concepts. Research objective is the analysis of theoretical provisions of the legislative equipment and texts of the civil legislation in a state language and bases on that to identificate mistakes in translation of legal rules, generalize problems of the low-quality text translation of acts in Kazakh, to draw conclusions on improvement of the legal equipment when developing acts in a state language. Proceeding from the generalized analysis some acts' texts of the Republic of Kazakhstan in a state language, the existing theoretical views and remarks stated by the author, options of correct translation of legal rules on kazakh language and improvemental ways of the legal equipment on the text translation of statutory legal acts into kazakh are offered. The solution of such important problem will promote to increase in legal culture of modern Kazakhstan society.